Epstein-Barr virus and human papillomaviruses as favorable prognostic factors in nasopharyngeal carcinoma: A nationwide study in Finland - Miia Ruuskanen; Heikki Irjala; Heikki Minn; Tero Vahlberg; Reija Randen‐Brady; Jaana Hagström; Stina Syrjänen; Ilmo Leivo (John Wiley and Sons Inc., 2022)
Background: Nasopharyngeal carcinoma (NPC) is related to Epstein‐Barr virus (EBV) in endemic areas; however, the role of viruses in nonendemic countries is unclear. Our nationwide study investigated the prevalence and prognostic significance of EBV and human papillomaviruses (HPVs) in Finnish NPC tumors.
Methods: We analyzed samples from 150 patients diagnosed between 1990 and 2009. Viral status was determined using EBV and HPV RNA in situ hybridizations, and p16 immunohistochemistry. Patient and treatment characteristics were obtained from patient records.
Results: In our white patient cohort, 93 of 150 (62%) patients were EBV‐positive and 21/150 (14%) patients were HPV‐positive with no coinfections. Thirty‐six (24%) tumors were negative for both viruses. The 5‐year disease‐specific survival for patients with EBV‐positive, HPV‐positive, and EBV/HPV‐negative tumors was 69%, 63%, and 39%, respectively. In multivariable‐adjusted analysis, overall survival was better among patients with EBV‐positive (P = .005) and HPV‐positive (P = .03) tumors compared to patients with EBV/HPV‐negative tumors.
Conclusions: In our low‐incidence population, EBV and HPV are important prognostic factors for NPC.